If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -9 = 3(-1c + 2) Reorder the terms: -9 = 3(2 + -1c) -9 = (2 * 3 + -1c * 3) -9 = (6 + -3c) Solving -9 = 6 + -3c Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '3c' to each side of the equation. -9 + 3c = 6 + -3c + 3c Combine like terms: -3c + 3c = 0 -9 + 3c = 6 + 0 -9 + 3c = 6 Add '9' to each side of the equation. -9 + 9 + 3c = 6 + 9 Combine like terms: -9 + 9 = 0 0 + 3c = 6 + 9 3c = 6 + 9 Combine like terms: 6 + 9 = 15 3c = 15 Divide each side by '3'. c = 5 Simplifying c = 5
| 1X+4X=58 | | -20(y+2)+6(4y-4)=3(y-6)+12 | | -0.24p+1.602=1.8 | | 12x-3=4x | | 3(x-2)-4=4x-2 | | 9y=2y+35 | | v^2-2=65 | | 2y+1=23 | | 12k-32=24 | | -n+1-7n=9-7n | | -3+6x=x+7 | | z+3.6=2.5 | | -0.24p+1.602=1.29 | | 1X+4Y=58 | | -5x-10=-3+2x | | 7(n-4)-(6-3n)=9n | | 0,001*0,001x=1/8 | | 2+3x=-5x-6 | | 2x-5=-2+x | | H=0.001x^2-X+27 | | 12h=72 | | (x+4)+(x+2)+(x+5)=2(x+1)+2(x+3) | | 90m^2+21mn-6n^2=0 | | T-75H=735 | | 9x+7-7x=4+x+5 | | -2=6+2x | | -20=b-5 | | 8-n=6+4n | | -9+7m=1+5m | | (m+2)(m-2)=0 | | 3(5-q)+6=9 | | 5(x+2)-(2x-7)= |